Risk Perception and Psychological Impact of COVID-19 Pandemic Among Healthcare Workers in Primary and Secondary Healthcare Settings in Qatar: A National Study - Nisha Kader; Bushra Elhusein; Samya Al Abdulla; Abdul Hakeem Hamza; Muna Al Maslamani; Prem Chandra; Rasheedali Perayil; Jojo Vincent; Josephine Gunashekaran; Majid Alabdulla (SAGE Publishing, 2021)
Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, primary and secondary healthcare workers (HCWs) have faced unprecedented stress, jeopardizing their mental well-being. Aims: To compare risk perception and psychological distress between primary and secondary HCWs. Method: A cross-sectional web-based survey was conducted with HCWs in Qatar from April 5 to July 5, 2020. Psychological distress and risk perception were assessed using the Kessler Psychological Distress Scale, a perceived COVID-19 risk questionnaire, and a sociodemographic questionnaire. Results: Of the 4417 participating HCWs, 3421 (90.3%) felt that their job increased their risk of COVID-19 exposure, 3759 (90.9%) accepted this as part of their job, and 3440 worried that this also increased the risk of exposure to their families. Moreover, 2911 (84.8%) believed that their employer would look after their needs if they contracted COVID-19. Moderate to severe psychological distress was present in 1346 (30.5%) HCWs. Primary HCWs were less likely to experience moderate to severe psychological distress than secondary HCWs (adjusted OR, 0.48; 95% CI 0.29-0.77, P  = .003). Secondary HCWs who worked in COVID-19 designated areas had greater psychological distress. Conclusions: HCWs' exposure to outbreaks has various psychological effects, which may have long-term consequences and affect their decision-making capacity. Strategies to enhance the mental well-being of HCWs exposed to COVID-19 should be introduced immediately.